2020
DOI: 10.3233/blc-200294
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Cancer Following Medicaid Expansion: No Changes in the Diagnosis of Muscle-Invasive Disease and Time to Treatment

Abstract: BACKGROUND: Bladder cancer patients who are insured experience improved outcomes. Medicaid expansion aimed to increase insurance coverage and improve access to care. However, the association between Medicaid expansion and stage at diagnosis or time to treatment for those with advanced bladder cancer is unknown. OBJECTIVE: We sought to determine to association of Medicaid expansion with stage at diagnosis, and time to treatment for patients with muscle-invasive bladder cancer. METHODS: A US-based cancer registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…32,39,40 Although prior work has examined the association between ME, timely treatment, and cancer survival, most of these studies have included all insurance types in their study cohort, which could mask the impact of the policy on Medicaid eligible patients who are most likely to benefit from ME. [18][19][20]32,38,41 By focusing our analysis on Medicaid and uninsured patients, we provide a more granular and arguably more precise estimate of the policy's effect on its target population. In our analysis of Medicaid and uninsured patients, the DID estimates for TTI and OS are larger in magnitude compared to previous studies that included all insurance types in their analysis of ME.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,39,40 Although prior work has examined the association between ME, timely treatment, and cancer survival, most of these studies have included all insurance types in their study cohort, which could mask the impact of the policy on Medicaid eligible patients who are most likely to benefit from ME. [18][19][20]32,38,41 By focusing our analysis on Medicaid and uninsured patients, we provide a more granular and arguably more precise estimate of the policy's effect on its target population. In our analysis of Medicaid and uninsured patients, the DID estimates for TTI and OS are larger in magnitude compared to previous studies that included all insurance types in their analysis of ME.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies using other data sources (including SEER or NAACCR) have found small improvements in 2‐year OS for lung and colorectal cancer associated with ME, but no significant changes for patients with breast or cervical cancer 32,39,40 . Although prior work has examined the association between ME, timely treatment, and cancer survival, most of these studies have included all insurance types in their study cohort, which could mask the impact of the policy on Medicaid eligible patients who are most likely to benefit from ME 18–20,32,38,41 . By focusing our analysis on Medicaid and uninsured patients, we provide a more granular and arguably more precise estimate of the policy's effect on its target population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, hospital-registry based studies of patients with genitourinary cancers derived from the National Cancer Database largely show declines in the rate of uninsurance following Medicaid expansion, but report variations in changes to stage of diagnosis and time to treatment. 13,[17][18][19][20] Appreciating the persistence of barriers to access elevates the importance of conducting studies at the level of the Medicaid insured population.…”
Section: Discussionmentioning
confidence: 99%